Building Capacity in Post-Conflict Countries - Mckechnie, Alastair J. (World Bank, Washington, DC, 2012)
This note looks at the challenge of capacity building in post conflict countries, including options for creating capacity and the trade-offs between speed and longer-term impact, the need to ensure that aid management agencies include sunset provisions, and six proposed general lessons for more sustainable capacity building.